CITATIONS AND INCENTIVES IN ACADEMIC CONTESTS. - Amegashie, J. Atsu (Economic Inquiry, 2020)
I consider a contest between scholars on the basis of three popular indices of citation. There exist equilibria in which there are more and better‐quality papers in the total citations contest than in the h‐index contest. In some cases, the total citations contest yields the same quality of papers but more papers than the Euclidean contest. As the cost of writing a paper increases,the h‐index is inferior to the total citations index in both the quality and quantity of papers. This result is partly driven by how the number of papers constrains how the h‐index counts citations.